Red Team Performance: Summary of Findings - Carayon, Pascale; Kraemer, Sara (My University, 2004)
This report summarizes a study the performance of the red team program at Sandia National Laboratories. This study describes the factors that contribute to and hinder red team performance, as well as various measures of red team performance.